Penerapan Metode PIPRECIA dan Multi-Attribute Utility Theory dalam Pemilihan Reporter Terbaik - Ardiansah, Temi; Putra, Ade Dwi (PT. SNN MEDIA TECH PRESS, 2024)
In the media industry, reporters play an important role in conveying accurate, fast, and credible information to the public. One of the main problems is subjectivity in evaluation, where personal preferences or the evaluator's bias can affect the final result. In addition, the scoring criteria used are sometimes not uniform or clear, resulting in a difference in perception of what actually constitutes the best reporter's measure. The purpose of applying the PIPRECIA and MAUT methods in selecting the best reporter is to provide an objective and measurable assessment of the reporter's performance based on several relevant criteria. The results of Ferdi's ranking won 1st place with a final score of 0.4358, indicating that he has the best performance in the assessment based on the set criteria, namely the quality of coverage, communication skills, speed of news delivery, and excellent integrity. The results of this ranking provide a clear insight into the performance of each reporter based on the PIPRECIA and MAUT methods. These results can be used as a reference for further decision-making regarding recognition or awards to reporters.